Micodegradação de Atrazina por isolados oriundos de sedimento fluvial de área agrícola - Corrêa, Cassiano Ricardo Reinehr (2021)
The national agricultural activity allocates 80 million hectares of Brazilian territory for harvesting, and of these, 77% are for temporary crops of cereals, legumes and oilseeds. Within this scenario, the herbicide atrazine is the fourth active principle most used in weed control in Brazilian agriculture. Due to its chemical structure being composed of a triazine ring substituted with chlorine, ethylamine and isopropylamine, it is a highly recalcitrant substance for biological degradation in the environment. The application of fungi in pesticide bioremediation processes has been widely studied, as they are easily adaptable and resistant organisms, and also have the ability to produce enzymes to metabolize several substances. In this context, the study aimed to evaluate whether fungi isolated from river sediments from areas of intense agricultural activity have the ability to biodegrade the herbicide atrazine. For this, initially, the fungi capable of producing ligninolytic enzymes using the oxidation of guaiacol were selected. Afterwards, the positive fungi were evaluated for their ability to tolerate different concentrations of the herbicide in a static experiment. The most tolerant were chosen to carry out the biodegradation test in a liquid medium plus 30 mg L-1 of atrazine for 21 days. For these fungi, morphological and molecular identification was performed. In the experiment that degraded the herbicide, the enzymatic activity of laccase and lignin peroxidase was determined and the phytotoxic potential of the degradation product was evaluated by bioassays with rocket seeds. After the tolerance experiments, it was observed that 5 fungal strains were able to tolerate the herbicide at concentrations from 30 to 200 mg L-1. However, in the biodegradation tests, only the F20 strain was able to biodegrade 25% of the atrazine, with the formation of the desethylatrazine molecule, characterized by FTIR and HPLC/MS analyses. In evaluating the enzymatic activity, the values obtained were not expressive, and it is not possible to relate the enzymes to biodegradation. In the phytotoxicity experiment there was no reduction in toxicity after biodegradation, because the desethylatrazine molecule is very similar to atrazine and the percentage obtained in the biodegradation was not able to biotransform the herbicide into other compounds. Despite the verification of the herbicide's effective mycodegradation capacity, the use of the F20 fungal strain for future biotechnological applications of bioremediation of soil or water contaminated with atrazine, require further studies aimed at enhancing its percentage of biodegradation.